Keeping Blue Collars in Green Cities: From TOD to TOM? - Dierwechter, Yonn A.; Pendras, Mark (Frontiers in Sustainable Cities, 2020)
Building on work that critiques smart growth's "industrial blind spot," we explore here the potential for ‘transit-oriented manufacturing’ (TOM) rather than transit-oriented development (TOD) in order to gain some purchase on visions for green city futures that include blue collars workers. The shift from TOD to TOM, we argue, involves some rethinking of what (and who) cities are for, and paying careful attention to how investments in transit infrastructure serve to define, materially and symbolically, urban and regional relations and identities. Through an engagement with the scholarship on planning for urban industry, smart growth, and transit-oriented development, we argue that the first challenge is to make TOM thinkable. By this we mean not only how we abstractly imagine or conceive future worlds, but also how we create and deploy practical vocabularies of deliberated urban change that actively help to mobilize new conversations about critical places in our changing and changeable cities and regions. We link this challenge of the ‘‘thinkability” of TOM to a brief case study in the city of Tacoma, WA.